2011
DOI: 10.1007/s10552-011-9825-5
|View full text |Cite
|
Sign up to set email alerts
|

Gestational diabetes and risk of incident primary cancer: a large historical cohort study in Israel

Abstract: GDM is associated with an increased risk of pancreatic cancer and hematologic malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 44 publications
3
39
1
1
Order By: Relevance
“…After having followed for 28-40 years, they found 5 new pancreatic cancer cases in women with GDM history and 49 without the history; the hazard ratio (HR) of GDM history was 7.1 (2.8-18.0) after adjusted for age at first observed birth and birth weight. Similar result was also observed in a recent cohort of 185315 women by Sella et al (2011). After average follow-up period of 5.19 years, they revealed an adjusted HR of GDM history versus non-GDM history as 7.06 (1.69-29.45).…”
Section: Gdm and Other Types Of Cancersupporting
confidence: 87%
“…After having followed for 28-40 years, they found 5 new pancreatic cancer cases in women with GDM history and 49 without the history; the hazard ratio (HR) of GDM history was 7.1 (2.8-18.0) after adjusted for age at first observed birth and birth weight. Similar result was also observed in a recent cohort of 185315 women by Sella et al (2011). After average follow-up period of 5.19 years, they revealed an adjusted HR of GDM history versus non-GDM history as 7.06 (1.69-29.45).…”
Section: Gdm and Other Types Of Cancersupporting
confidence: 87%
“…Odds ratio increased risk point estimate (Troisi et al 1998, Lawlor et al 2004, Perrin et al 2008 and one study reporting a negative risk point estimate (Sella et al 2011). The pooled OR did not find any association between gestational diabetes and BC (OR 1.06, 95% CI 0.79-1.40) while significant heterogeneity was present (I 2 Z68.81, PZ0.01).…”
Section: Study Name Statistics For Each Study Odds Ratio and 95%cimentioning
confidence: 74%
“…Gestational diabetes has been found to be protective in one study (Rollison et al 2008) while other studies reported an increased risk (Perrin et al 2008) or no association between the two (Troisi et al 1998, Lawlor et al 2004, Sella et al 2011). This discrepancy is also present within studies investigating type 2 diabetes mellitus and studies investigating the aetiology of BC in males.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations